Towards a Tawhidic framework in Islamic higher education curriculum: a comparative study of Indonesia and Malaysia - Subhan, Subhan; Ghufran, Zaki; Mufrodi, Mufrodi; Sahid, Mohamad Khaidir (State Islamic Institute Of Kudus, 2024)
This study aims to explore the key aspects of incorporating Islamic values into the curriculum design for Islamic higher education in Indonesia and Malaysia. By employing a qualitative approach and comparative study, this research examines two educational paradigms: the integration of knowledge and the Islamization of knowledge. Both models aim to bridge the gap of the dichotomy between modern sciences and Islamic values that has contributed to fragmented graduate competencies. Focusing on Arabic language education, the study highlights its pivotal role among the subjects taught in Islamic universities to facilitate the internalization of Islamic values and a medium for engaging with Islamic literature. As a medium for delivering Islamic teachings, Arabic language education is also essential for exploring Islamic primary texts such as the Qur’an and Hadith. Therefore, a strategically designed Arabic language curriculum is crucial, serving as a critical mechanism for internalizing Islamic values in Islamic universities. The findings reveal that both institutions share common goals: cultivating graduates who embody academic excellence alongside deep-rooted Islamic values and intellectual consciousness.